Zakon o obveznih zavarovanjih v prometu, evropska zavarovalniška direktiva in slovenski predhodni vprašanji za Sodišče EU - Varanelli, Luigi (Pravni letopis, 2014)
In the contribution author analyses some controversial aspects of directive on insurance against civil liability in respect of the use of motor vehicles. In the analysis of the concept of vehicle he defends a restrictive interpretation, basing on the teleological interpretation of the regulation concerning the automobile third party insurance. More problematic is the position of so called compensation body, to which the claim could be addressed, when the liable insurance undertaking or its representative in the fixed period does not answer to the claim of the injured party. The full efficiency of the 6th Article of directive on insurance against civil liability in respect of the use of motor vehicles, that has introduced the compensation body, requires that the above mentioned body is not seen as a mediator between the liable insurance undertaking and the insured, but as a subject being liable to compensate the damages, if the conditions provided by the directive have been realized.
Keywords: avtomobilsko zavarovanje; cestni promet; European Union; Evropska unija; motorna vozila; zavarovalno pravo